Interference among the Processing of Facial Emotion, Face Race, and Face Gender - Li, Yongna; Tse, Chi-Shing (Frontiers in Psychology, 2016)
People are able to simultaneously process multiple dimensions of facial properties. Facial processing models are based on the processing of facial properties. This paper examined the processing of facial emotion, face race and face gender using categorization tasks. The same set of Chinese, White and Black faces, each posing a neutral, happy or angry expression, was used in three experiments. Facial emotion interfered with face race in all the tasks. The interaction of face race and face gender was found in the race and gender categorization tasks, whereas, the interaction of facial emotion and face gender was significant in the emotion and gender categorization tasks. More importantly, there was a three-way interaction in all the tasks. These results provided evidence for a symmetric interaction between variant facial properties (emotion) and invariant facial properties (race and gender). This suggests that multiple facial properties can be interactively processed.